PENGUNGKAPAN CSR PADA HUBUNGAN PROFITABILITAS DAN STUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Nindita, Nansi Ria; Saiful, Saiful; Coryanata, Isma (UNIB Press, 2017)
The purpose of this study is to empirically prove the effect of profitability, managerial ownership on firm value, and to prove empirically that CSR disclosure is able to moderate the relationship between profitability and firm value.The population of this research is all mining sector companies listed on the IDX in 2013-2015 totaling 41 companies. Samples were taken using the purposive sampling technique, obtained a sample of 34 companies. The analytical method used is multiple linear regression.The results of this study indicate that the profitability variable has a negative effect on firm value. Managerial ownership has no effect on firm value. Institutional ownership has a negative effect on firm value. CSR disclosure moderates the relationship between profitability and firm value.